On the adsorption behavior of biotin-binding proteins on gold and silica - Wolny, Patricia Maria; Spatz, Joachim P.; Richter, Ralf Peter (Langmuir, 2010)
Streptavidin (SAv), avidin (Av), and neutravidin (NAv) have become widely used molecular tools in biotechnology thanks to their remarkable affinity for biotin. Their tetravalency renders these molecules particularly interesting for the functionalization of solid−liquid interfaces. Using the quartz crystal microbalance with dissipation monitoring, we systematically investigate the deposition of biotin-binding proteins to two surfaces that are popular in biotechnology: gold and silica. We find that simple physisorption of biotin-binding proteins is a viable method to confer biotin-binding functionality to gold surfaces. Both SAv and Av form dense, stable protein monolayers that retain biotin-binding activity and are largely inert to the unspecific binding of bovine serum albumin. Furthermore, we report that SAv resists adsorption to silica over a wide range of pH and ionic strength. The contrast in the binding behavior of SAv on silica and on gold suggests a simple strategy for the selective biofunctionalization of nano- or microstructured surfaces.